William Elong: An ICT innovator - Franck Kuwonu (Africa Renewal, 2018)
The news wasn’t big enough to excite international media, but it was an exciting development this year in Cameroon when Will&Brothers, a local engineering and consulting company, unveiled the first-ever drone made in Cameroon.